Inductive Approach to Teaching Grammar - Islamova Taxira Rixsibayevna (International Journal on Orange Technologies, 2022)
This article examines teaching grammar inductively for intermediate level learners. There are many approaches to teaching grammar at different levels. The approach which provides favorable conditions for the speedy development of correct and more flexible language use is mentioned below.